Management of Bangladesh's national security problems - Hossain, Ishtiaq (Taylor & Francis, London, UK, 1991)
Argues that the way Bangladesh's security problems are handled should differ from the traditional ways that security are dealt with in developed states. National security in the Bangladesh context; Factors affecting the national security of Bangladesh; Sources of threat; Suggestions for meeting national security challenges.